The tyranny of merit [compact disc, unabridged] : what's become of the common good? - Sandel, Michael J. (Macmillan Audio, 2020)
Politics is fraught with rancor and resentment. Decades of rising inequality and stalled mobility have fueled a populist revolt against elites. But while the pundits focus on wages and jobs, they are missing a big part of the story: social esteem, and the broader moral dimensions of our current crisis. In recent decades, mainstream politicians across the aisle, from Reagan to Obama, have offered rhetoric of rising: everyone should be given an equal chance to get ahead. But the relentless focus on "equal opportunity" ignores the morally corrosive attitudes that even a fair meritocracy generates. Among the winners, it generates hubris; among the losers, humiliation. Meritocratic hubris reflects the tendency of winners to inhale too deeply of their success, to forget the luck and good fortune that helped them on their way.